Perceptions and knowledge of secondary school students on Bukit Nanas Forest Reserve as urban forest in Kuala Lumpur - Marzuki, Mohd Jamaluddin (2018)
Urbanization is growing more rapidly that the urban expansion has led to land use changes which can adversely impact the environment, economy and social aspects. Urban forest and other green infrastructure in cities can provide numerous benefits to the urban citizens. Bukit Nanas Forest Reserve (BNFR) is a forest reserve strategically located in Kuala Lumpur city. In order to preserve the urban forest the awareness of the urban forest benefits is important especially to younger generation. Therefore, this study assessed the perceptions and knowledge on the urban forest importance and benefits among students surrounding BNFR area. Sekolah Menengah Kebangsaan Convent Bukit Nanas, Sekolah Menengah Kebangsaan St. John and Sekolah Menengah Kebangsaan Confucion were selected as the schools within one kilometer radius from BNFR. Questionnaires were collected from 348 students comprising of male and female students. The finding showed that students were aware of the existence of urban forests in Kuala Lumpur and had knowledge on BNFR importance as urban forests as well as its role in controlling surrounding temperatures. Students’ knowledge was also influenced by their perceptions as there was a correlation between knowledge and perceptions. These findings suggest that secondary school students have a positive perception and knowledge of BNFR and this implies that the young generation has potential to support the necessities to conserve the urban forest areas for its benefits. This study will be generally beneficial to urban citizens and provide an information to relevan agencies in order to plan and enhanced the function and services of the BNFR.